Soft multi-modal thermoelectric skin for dual functionality of underwater energy harvesting and thermoregulation. (May 2022) - Jung, Yeongju; Choi, Joonhwa; Yoon, Yeosang; Park, Huijae; Lee, Jinwoo; Ko, Seung Hwan
Abstract: Sustaining a long-term but viable power source for underwater electronics has been an engineering conundrum due to a lack of feasible physical mechanisms to harvest energy in the underwater environment. In this regard, thermoelectricity, which converts heat into electricity, can suggest a potent solution, since the ocean and other water bodies maintain the constant water temperature and therefore serve as a permanent thermal differential. In addition to energy harvesting, the same thermoelectric device can be also utilized to both heat and cool, thereby providing an effective means of controlling the temperature of the arbitrary subject in the underwater environment. In this light, we present a soft and stretchable multi-modal thermoelectric skin (TES) that can both (i) generate electricity across the temperature differential between the ocean water and the human body and (ii) thermoregulate the body temperature in the underwater environment. The soft and elastic nature of TES enables an intimate and thorough contact with the deformable and irregular surfaces of the human skin, therefore maximizing the heat conduction at the human-device interface that the rigid or flexible thermoelectric devices can not fully attain. To the authors' best knowledge, TES produces the highest electrical power density when compared to the stretchable thermoelectric devices reported so far, mainly owing to its optimum design factors. Along with the outstanding device performance, the underwater environment further boosts the thermoelectric efficiency of TES both in energy harvesting and thermoregulatory perspectives due to the much more favorable thermal properties of water than those of air. Furthermore, to verify the practical usage of TES and demonstrate its high wearability, we incorporated multiple TES units into the neoprene dry-suit. The TES units can self-power multiple embedded sensors that wirelessly monitor the physiological condition and further provide the spatial information of the tactical diver, such that the TES units and embedded system can function as a wearable underwater rescue platform. Lastly, the temperature feedback loop algorithm embedded in the thermoregulatory system allows the TES units to constantly regulate the temperature of the human body and thus prevent underwater hypo-/hyperthermia. Graphical Abstract: We present the first demonstration of a soft and stretchable multi-modal underwater thermoelectric skin that facilitates underwater operation by offering wireless self-powered and thermoregulatory functionalities. The energy harvesting mode of thermoelectric skin generates the electricity by the thermal differential to self-power the sensors that provide physical and electrophysiological signals (ECG, gyro, and pressure sensors) of the diver in real-time. The other mode actively regulates the body temperature to be highly constant by thermoelectric cooling and heating based on the embedded feedback control algorithm. We expect that this work will provide valuable assets and insights into the development of future underwater electronics and energy harvesting technologies to facilitate underwater operation. ga1 Highlights: We developed the soft multi-modal thermoelectric skin for underwater energy harvesting and thermoregulation. Thermoelectric skin generates electricity from the consistent thermal differential between the human body and ocean water. The generated energy is used to operate the wireless sensors to monitor the diver's physiological condition. Also, the generated energy is used to operate the thermoelectric cooling/heating to regulate the diver's body temperature.